Effect of bilberry juice on indices of muscle damage and inflammation in runners completing a half-marathon: a randomised, placebo-controlled trial. Issue 1 (2nd May 2018) - Lynn, Anthony; Garner, Samantha; Nelson, Nichola; Simper, Trevor N.; Hall, Anna C.; Ranchordas, Mayur K.
Abstract: Background: Emerging evidence indicates that fruits rich in polyphenols may attenuate exercise-induced muscle damage and associated markers of inflammation and soreness. This study was conducted to determine whether bilberry juice (BJ), which is particularly rich in polyphenols, reduces markers of muscle damage in runners completing a half marathon. Methods: A total of 21 recreationally trained runners (age 30.9 ± 10.4 y; mass 71.6 ± 11.0 kg; M = 16; F = 5) were recruited to a single blind, randomised, placebo-controlled, parallel study. Participants were block randomised to consume 2 × 200 ml of BJ or energy-matched control drink (PLA) for 5 d before the Sheffield Half Marathon, on race day, and for 2 days post-race. Measurements of delayed onset muscle soreness (DOMS), muscle damage (creatine kinase; CK) and inflammation (c-reactive protein; CRP) were taken at baseline, pre-race, post-race, 24 h post-race and 48 h post-race. The effect of treatment on outcome measures was analysed using magnitude-based inferences based on data from 19 participants; 2 participants were excluded from the analyses because they did not provide samples for all time points. Results: The half marathon caused elevations in DOMS, CRP and CK. BJ had a possibly harmful effect on DOMS from pre-race to immediately post-race (11.6%, 90% CI ± 14.7%), a likely harmful effect on CRP from pre-race to 24 h post-race (mean difference ES 0.56, 90% CI ± 0.72) and a possibly harmful effect on CRP from pre-race to 48 h post-race (ES 0.12, 90% CI ± 0.69). At other time points, the differences between the BJ and PLA groups in DOMS and CRP were unclear, possibly trivial or likely trivial . Differences in the changes in CK between BJ and PLA were unclear at every time point other than from baseline to pre-race, where BJ had a possibly harmful effect on reducing muscle damage (ES 0.23, 90% CI ± 0.57). Conclusion: Despite being a rich source of antioxidant and anti-inflammatory phytochemicals, BJ evoked small to moderate increases in exercise-induced DOMS and CRP. Further larger studies are required to confirm these unexpected preliminary results.